Primjena input-output modela u analizi potrošnje vode kao inputa u gospodarstvu Hrvatske - Gelo, Tomislav (Array, 2021)
The paper analyses the application of the input-output model in water consumption. Water as a limited resource and input in the Croatian economy is researched through intersectoral relationships of sectors in the national economy breakdown, based on two hybrid input-output models, for 2004 and 2010. The change in time relationship between the economy and water resources is also analysed. Sectors are mutually connected. Therefore, each change in aggregate consumption will affect the water consumption distribution in each sector. This fact results in the importance of analysing intermediary relationships at the level of the national economy, and consequently, the impact of the national economy on the available water resources. The paper uses the hybrid input-output model for water consumption, created for 2004 and 2010, based on the available publications of the Croatian Bureau of Statistics and the Croatian Environmental Protection Agency. The base publications for creating the model are supply and use tables, from which symmetrical input-output tables for 2004 and 2010 were extrapolated, and the data on water distribution in 2004 and 2010. In the hybrid model, the entire Croatian economy was broken down into 22 sectors. Each sector was created by consolidating various activities from the National Classification of Activities (NKD) in 2002 and 2007. The model determines the intensities of direct and indirect water consumption, and consequently, the total water consumption intensity, and direct and total consumption multipliers. The model results for the stated years indicate that there are only several industrial sectors in the Croatian economy which have a dominant direct impact on water resources (electricity generation, Coke and refined petroleum products and Chemicals and chemical products). A decrease in the impact on water resources in Croatia can be achieved by decreasing the consumption intensity of water resources in the observed sectors.